A Comparative Case Study of Business Process Model with Petri Nets and Process Activity Diagram - Devi, Aruna T; Kumudavalli, M.V (International Journal of Computer Sciences and Engineering, 2025)
Business with information technology has bought a revolutionary change in the digital world in terms of the huge amount of data available for processing. Mining techniques are playing a key role in enterprises as it is being used to search vast amounts of data for vital insight and knowledge. The sheer amount of data is posing challenges in terms of representation, analysis etc., which has given emphasis to pictorial representation of the same which for easy visualization and understanding. The mining tools are automated software tools used to achieve business intelligence by finding hidden relations, and predicting future events from vast amounts of data. This uncovered knowledge helps in gaining completive advantages, better customer relationships, etc. To process the data the techniques of process mining is used to discover and analyse the process. Process activity diagrams are often used to model business processes. One of the important modelling artefacts used is the activity diagrams which are further used to model the sequence of actions as part of the process flow. Process mining techniques use Petri nets which are best investigated process modelling language allowing for the modelling of concurrency. This paper emphasizes the comparison of the given process activity model to corresponding petri nets for analysis and verification. The process activity diagram and petri nets are used to demonstrate the applicability of process mining techniques